Perspectives on Preschool curriculum in Portugal - Carrachás, N (2021)
The present communication is focused on the curriculum of preschools in Portugal (ages 3 to 6) and how preschool educators and 1st cycle (ages 6 to 10) teachers, as well as preschool children’s parents perceive it. Firstly, preschool education is contextualized in order to better frame the need for an active investment in the valuing of this educational level. Given its short existence, accompanied by advancements and setbacks, the idea often perceived in social discourse about preschool education in Portugal is often not one of an activity aimed at the global development of children, as assistentialist conceptions persist. However, while there isn’t a structured curriculum for preschool, there are Curricular Guidelines for Preschool Education (CGPE), a set of general principles which contribute to the childhood educators’ decisions about their educational practice and the educational intentionality of the activities developed with children. This document is a referential for the national network of preschool education for the construction of curriculum, which retains a wide margin of decision for the contextualization and differentiation of curriculum, acknowledging the childhood educators’ role as a curriculum decision maker. The aim of this study was to understand the conception that preschool teachers, 1st cycle teachers and some parents have about this level of education as well as to understand if they recognize the importance of developing personal and social skills together with other content areas which might be a facilitating scafold for the entrance in the following cycle. This study, using a mixed methodology, included semi-structured interviews to preschool educators (eight interviewees), and questionnaires to 1st cyle teachers (fourty nine) and parents (seventy-eight) of four schools in a region of inner Portugal, the district of Beja. The research followed the ethical norms for research in the social sciences, namely informed consent by participants and preservation of anonymity. Data gathering instruments were approved by the Ministry of Education as well as by the pedagogical councils and directors of the four school clusters involved. The main results show that all the preschool educators surveyed base their curriculum building process on the CGPE, some referring to this document as their «Bible» and also as the foundation of their planning and assessment practices. However important the document is deemed, it is not the sole foundation for their curricular decision-making, as children themselves and schools’ other internal documents and projects are also taken into account. Although primary school teachers know about the existence of the CGPE, they don’t demonstrate a broad understanding about its content, although they identify practices of coordination with preschool educators to prepare the students’ transition between educational cycles. They also recognize that the work carried out in preschool aims to facilitate future learning processes by the children. On the other hand, parents revealed a more passive attitude towards their children’s activities in preschool.